Masseteric-Facial Anastomosis: A Report of Three Cases - Breno Alexander Bispo (Thieme Revinter Publicações Ltda., 2021)
Intoduction The pathways of the facial nerve are variable, and knowledge of that is essential. The worst impact caused by facial paralysis is related to quality of life, especially regarding the self-esteem and social acceptance on the part of the patients, leading to social isolation and disruption on their mental health. Case Report A 33-year-old female patient, with a stage-T3 acoustic neurinoma, presented with a moderate dysfunction (grades II to III) according to the House-Brackmann (HB) Facial Nerve Grading System. A 43-year-old male patient, with a stage-T4B trigeminal schwannoma, underwent a resective surgery and presented grade-VI dysfunction according to the HB scale. And a female patient with a stage-T4A acoustic neurinoma presented grade-IV dysfunction according to the HB scale. Discussion We performed a literature review of papers related to surgeries for masseteric-facial nerve anastomosis and compiled the results in table; then, we compared these data with those obtained from our cases. Conclusion The masseteric nerve is the one that shows the best prognosis among all the cranial nerves that could be used, but it is also necessary to perform well the surgical technique to access the facial branch and consequently achieve a better masseteric-facial nerve anastomosis.